Adaptive terminal angle constraint interception against maneuvering targets with fast fixed‐time convergence. (1st March 2018) - Zhang, Yao; Tang, Shengjing; Guo, Jie
Summary: In this paper, a modified adaptive fast nonsingular terminal sliding mode guidance law is proposed based on the theory of fixed‐time convergence, which is applied for intercepting maneuvering targets considering terminal angle constraint. The proposed guidance law achieves system stabilization within bounded settling time independent on initial conditions and provides no singularity and globally rapid convergence property by accelerating the convergence rate when the system is close to the origin. The upper bound of settling time can be obtained in advance by the controller's parameters. Besides, in order to achieve chattering‐free property, a continuous adaptive switching control is introduced and the achieved acceleration‐magnitude constraints are rigorously enforced. Finally, the fixed‐time convergence of the sliding mode manifold and the system states is demonstrated by Lyapunov stability theory. Extensive numerical simulations are presented to validate the efficiency and superiority of the proposed guidance law.